Improving Household Survey Instruments for Understanding Agricultural Household Adaptation to Climate Change : Water Stress and Variability - Bandyopadhyay, Sushenjit (World Bank, Washington, DC, 2013)
The Living Standards Measurement Study (LSMS) surveys which have collected information on many dimensions of household well-being for over 36 countries since 1980 are one of the most important data sources for informing policy making on development. The LSMS surveys have been used to assess household welfare, to understand household behavior, and to evaluate the welfare impact of various government policies. These surveys, however, lack well-designed instruments for understanding farm-level adaptation behavior to climate variability, in particular water resource variability and stress in agriculture. For the purpose of improving the quality, relevance and sustainability of smallholder agricultural data in Sub-Saharan Africa, the Living Standards Measurement Study-Integrated Surveys on Agriculture (LSMS-ISA) project was started with a grant from the Bill and Melinda Gates Foundation, and is implemented by the LSMS team in the Development Research Group (DECRG) of the World Bank. Under the LSMS-ISA initiative, the World Bank is supporting seven countries in Sub-Saharan Africa, namely Ethiopia, Malawi, Mali, Niger, Nigeria, Tanzania, and Uganda, to establish systems of multi-topic, panel household surveys with a strong focus on agriculture. The surveys collect essential information to improve our understanding of economic development in Africa, particularly with regards to agriculture and linkages between farm and non-farm activities.